อิทธิพลของสัดส่วนอินเดียมและค่าความหนาของชั้นแทรกอินเดียมแกลเลียมอาร์เซไนด์ ที่มีต่อโครงสร้างขนาดนาโนของแกลเลียมแอนติโมไนด์ - กมลชนก ขอกลาง (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this thesis, we report on the growth, structural and optical properties of GaSb nanostructures with InGaAs insertion layers. In this work, type-II GaSb nanostructures are epitaxially grown on (100) GaAs substrates by self-assembled growth using an MBE equipped with Sb cracker cell. Prior to the growth of GaSb layers, 0, 1, 2, 3 and 4 monolayers (MLs) of InxGa1-xAs are inserted with various indium compositions (7%, 15%, 20% and 25%). With InGaAs insertion layers, the dot density decreases about one order of magnitude (to 109 cm-2) less than that of GaSb/GaAs sample without insertion layer at the same growth condition. The shape and size of nanostructures change substantially. The GaSb/GaAs structures have dome-shaped with elliptical base. The elongation direction of the base changes from [110] to [1-10] when InxGa1-xAs insertion layers are introduced. The uniformity of GaSb QDs improves when the indium content and thickness of InGaAs insertion layers increase. The change in their morphology is due to modified strain energy at different values of indium compositions and thickness in InGaAs insertion layers. Photoluminescence (PL) of the capped samples shows that PL intensity increases with the increasing indium content. This indicates that the crystalline quality of GaSb nanostructure is improved by insertion of InGaAs layer.